Planty Childhoods: Theorising with a Vegetal Ontology in Environmental Education Research - Sneha Parmar; Karen Malone; Tracy Charlotte Young (Australian Journal of Environmental Education)
This paper explores the potential for extending relational ontologies to include a specific focus on human-plant relations. We theorise the emergence of a vegetal ontology, as a novel way of working and remaking theories around human-plant relations that can be applied to the field of environmental education. A vegetal ontological approach, as applied in the environmental education research project that informs this article, abandons hierarchical comparisons of plants, which are often historically positioned as “lesser species,” mere “objects” and “resources” even. We start our paper with a modest review of key theoretical approaches informing past and recent environmental education studies on child-plant relations. We then return to the discussion started within the introduction to the paper on how we have theorised a vegetal ontology as a mode of a relational ontology focussing particularly on human-plant relations and drawing on posthumanist, new materialist and Indigenous approaches. To conclude the paper, we then put this newly named vegetal ontology to work. We apply it to a recent study on childhood-plant encounters where researchers engaged with young children and their families in a botanical garden setting and a group of environmental education elders reflected on the significance of plant relations in their childhoods.